The interplay of segmental and suprasegmental features in ESL/EFL reading aloud performance - Irawan, Lalu Ari; Ahmad, Ramli (Journal of Applied Studies in Language, 2025)
Effective spoken communication is influenced by intelligibility and comprehensibility, both of which are shaped by segmental and suprasegmental features of pronunciation. This study aims to examine how segmental and suprasegmental pronunciation features influence the intelligibility of Indonesian EFL learners during reading-aloud tasks. The study used a descriptive qualitative research method and involved 5 senior members of the Global English Community (GEC) at Mandalika University of Education (UNDIKMA) as participants. The data consisted of recorded speech produced during reading-aloud sessions and were collected through direct observation and expert rating by a native-speaker. The analysis focused on segmental features (vowel and consonant production, including monophthongs, diphthongs, and silent-letter words) and suprasegmental features (word stress and voice quality). The findings indicated that segmental inaccuracies particularly in English sounds not found in Indonesian caused the greatest reduction in intelligibility because they frequently altered word meaning. In contrast, suprasegmental issues such as misplaced stress and limited voice quality reduced naturalness and listener processing but did not affect meaning. These results indicated that pronunciation instruction for Indonesian EFL learners should prioritize segmental accuracy while still integrating suprasegmental training to support overall speech clarity.